2022
DOI: 10.3390/rs14194737
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Sea Surface Temperature by Combining Interdimensional and Self-Attention with Neural Networks

Abstract: Sea surface temperature (SST) is one of the most important and widely used physical parameters for oceanography and meteorology. To obtain SST, in addition to direct measurement, remote sensing, and numerical models, a variety of data-driven models have been developed with a wealth of SST data being accumulated. As oceans are comprehensive and complex dynamic systems, the distribution and variation of SST are affected by various factors. To overcome this challenge and improve the prediction accuracy, a multi-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Since oceans have extensive and complex dynamic systems, the distribution and variation of SST are dependent on different factors. Multi variable SST prediction is a suitable technique for overcoming this issue [52]. Accordingly, we utilized different parameters for time-series SST prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since oceans have extensive and complex dynamic systems, the distribution and variation of SST are dependent on different factors. Multi variable SST prediction is a suitable technique for overcoming this issue [52]. Accordingly, we utilized different parameters for time-series SST prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that air pressure and water temperature had similar weights and were significantly more important than wind direction and wind speed. However, there are different statements about important features that affect SST in the literature [52][53][54]. Wind speed affects the vertical heat flux, which could change SST [55].…”
Section: Discussionmentioning
confidence: 99%
“…Tian [30] proposed an electronic transition-based BBPSO for high-dimensional problems. Guo [31] proposed the TBBPSO algorithm, which enhances the local minimum escape capability of the proposed method. Guo [32] proposed BPSO-CM, where particle swarms are given enhanced global search capabilities.…”
Section: Related Workmentioning
confidence: 99%
“…Since the ocean is a comprehensive and complex dynamic system, the distribution and variability of SST are affected by a variety of factors. In the contribution by Guo et al, entitled "Prediction of Sea Surface Temperature by Combining Interdimensional and Self-Attention with Neural Networks," a multivariate long short-term memory (LSTM) model is proposed that uses wind speed and air pressure at sea level as inputs along with SST in order to overcome this problem and improve prediction accuracy [12]. In addition, for model optimization, a position encoding matrix and multi-dimensional input are studied.…”
Section: Overview Of Contributionsmentioning
confidence: 99%